PLEASE HELP Frank's dog weighs 4.25 times more than his
2 answers:
Answer:
58.65
Step-by-step explanation:
13.8x4.25=58.65
Answer:
58.65
Step-by-step explanation:
13.8 times 4.25 equals 58.65
You might be interested in
Answer:
![\large\boxed{\left(\dfrac{x}{2}-\dfrac{y}{2}\right)\left(\dfrac{x}{2}+\dfrac{y}{2}\right)=\dfrac{x-y}{2}\cdot\dfrac{x+y}{2}}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%5Cleft%28%5Cdfrac%7Bx%7D%7B2%7D-%5Cdfrac%7By%7D%7B2%7D%5Cright%29%5Cleft%28%5Cdfrac%7Bx%7D%7B2%7D%2B%5Cdfrac%7By%7D%7B2%7D%5Cright%29%3D%5Cdfrac%7Bx-y%7D%7B2%7D%5Ccdot%5Cdfrac%7Bx%2By%7D%7B2%7D%7D)
Step-by-step explanation:
![\dfrac{x^2}{4}-\dfrac{y^2}{4}=\dfrac{x^2}{2^2}-\dfrac{y^2}{2^2}\qquad\text{use}\ \left(\dfrac{a}{b}\right)^n=\dfrac{a^n}{b^n}\\\\=\left(\dfrac{x}{2}\right)^2-\left(\dfrac{y}{2}\right)^2\qquad\text{use}\ (a-b)(a+b)=a^2-b^2\\\\=\left(\dfrac{x}{2}-\dfrac{y}{2}\right)\left(\dfrac{x}{2}+\dfrac{y}{2}\right)=\dfrac{x-y}{2}\cdot\dfrac{x+y}{2}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%5E2%7D%7B4%7D-%5Cdfrac%7By%5E2%7D%7B4%7D%3D%5Cdfrac%7Bx%5E2%7D%7B2%5E2%7D-%5Cdfrac%7By%5E2%7D%7B2%5E2%7D%5Cqquad%5Ctext%7Buse%7D%5C%20%5Cleft%28%5Cdfrac%7Ba%7D%7Bb%7D%5Cright%29%5En%3D%5Cdfrac%7Ba%5En%7D%7Bb%5En%7D%5C%5C%5C%5C%3D%5Cleft%28%5Cdfrac%7Bx%7D%7B2%7D%5Cright%29%5E2-%5Cleft%28%5Cdfrac%7By%7D%7B2%7D%5Cright%29%5E2%5Cqquad%5Ctext%7Buse%7D%5C%20%28a-b%29%28a%2Bb%29%3Da%5E2-b%5E2%5C%5C%5C%5C%3D%5Cleft%28%5Cdfrac%7Bx%7D%7B2%7D-%5Cdfrac%7By%7D%7B2%7D%5Cright%29%5Cleft%28%5Cdfrac%7Bx%7D%7B2%7D%2B%5Cdfrac%7By%7D%7B2%7D%5Cright%29%3D%5Cdfrac%7Bx-y%7D%7B2%7D%5Ccdot%5Cdfrac%7Bx%2By%7D%7B2%7D)
Answer: 4x^2
Step-by-step explanation:
verified answer by Brainly
Answer:
93 degrees
Step-by-step explanation:
Answer:
![(1-sinA-cosA)^2 = 2(1-sinA)(1-cosA)\\Solution,\\L.H.S. = (1-sinA-cosA)^2 = [(1-sinA)-cosA]^2\\~~~~~~~~~~=(1-sinA)^2-2cosA(1-sinA)+cos^2A\\~~~~~~~~~~=1-2sinA+sin^2A-2cosA(1-sinA)+cos^2A\\~~~~~~~~~~=1-2sinA+sin^2A+cos^2A-2cosA(1-sinA)\\~~~~~~~~~~=1-2sinA+1-2cosA(1-sinA)\\~~~~~~~~~~=2-2sinA-2cosA(1-sinA)\\~~~~~~~~~~=2(1-sinA)-2cosA(1-sinA)\\~~~~~~~~~~=(1-sinA)(2-2cosA)= 2(1-sinA)(1-cosA)](https://tex.z-dn.net/?f=%281-sinA-cosA%29%5E2%20%3D%202%281-sinA%29%281-cosA%29%5C%5CSolution%2C%5C%5CL.H.S.%20%3D%20%281-sinA-cosA%29%5E2%20%3D%20%5B%281-sinA%29-cosA%5D%5E2%5C%5C~~~~~~~~~~%3D%281-sinA%29%5E2-2cosA%281-sinA%29%2Bcos%5E2A%5C%5C~~~~~~~~~~%3D1-2sinA%2Bsin%5E2A-2cosA%281-sinA%29%2Bcos%5E2A%5C%5C~~~~~~~~~~%3D1-2sinA%2Bsin%5E2A%2Bcos%5E2A-2cosA%281-sinA%29%5C%5C~~~~~~~~~~%3D1-2sinA%2B1-2cosA%281-sinA%29%5C%5C~~~~~~~~~~%3D2-2sinA-2cosA%281-sinA%29%5C%5C~~~~~~~~~~%3D2%281-sinA%29-2cosA%281-sinA%29%5C%5C~~~~~~~~~~%3D%281-sinA%29%282-2cosA%29%3D%202%281-sinA%29%281-cosA%29)